Therapeutic Perspectives on Chia Seed and Its Oil: A Review - Parker, John; Schellenberger, Amanda N.; Roe, Amy L.; Oketch-Rabah, Hellen; Calderón, Angela I. (Planta Medica, 2018)
The attraction of novel foods proceeds alongside epidemic cardiovascular disease, diabetes, obesity, and related risk factors. Dieticians have identified chia (Salvia hispanica) as a product with a catalog of potential health benefits relating to these detriments. Chia is currently consumed not only as seeds, but also as oil, which brings about similar effects. Chia seeds and chia seed oil are used mainly as a food commodity and the oil is also used popularly as a dietary ingredient used in various dietary supplements available in the U. S. market. Chia seed is rich in α-linolenic acid, the biological precursor to eicosapentaenoic acid, a polyunsaturated fatty acid, and docosahexaenoic acid. Because the body cannot synthesize α-linolenic acid, chia has a newfound and instrumental role in diet. However, the inconclusive nature of the scientific communityʼs understanding of its safety warrants further research and appropriate testing. The focus of this work is to summarize dietary health benefits of S. hispanica seed and oil to acknowledge concerns of adverse events from its ingestion, to assess current research in the field, and to highlight the importance of quality compendial standards to support safe use. To achieve this end, a large-scale literature search was partaken on the two well-known databases, PubMed and SciFinder. Hundreds of articles detailing such benefits as decreased blood glucose, decreased waist circumference and weight in overweight adults, and improvements in pruritic skin and endurance in distance runners have been recorded. These benefits must be considered within the appropriate circumstances.
Keywords: chia seed; chia seed oil; Salvia hispanica; biological activity; α-linolenic acid; Lamiaceae